IFRS disclosures and the dynamics of climate change: Analysis of South African manufacturing companies. - Mwzwandile, Mzwandile; Mishelle Doorasamy; Odunayo Magret Olarewaju (International Journal of Environmental, Sustainability, and Social Science, 2026)
The planet is gradually deteriorating due to climate change. Climate change is created by shifts in temperatures and weather patterns. Changes in temperatures might be natural, however, since the nineteenth century, human beings have made a significant contribution to climate change by not being environmentally conscious when burning fossil fuels, deforestation, using fertilisers and using fluorinated gases. Consequently, adding vast quantities of greenhouse gases to those naturally occurring in the atmosphere results in a rise in the greenhouse effect and global warming. Climate change affects not only human and natural systems but also the transparency of companies in making their financial disclosure during such climate conditions. The companies can be transparent by using the climate accounting tool to measure and report on the organisation's climate impact through direct and indirect emissions. Given the non-disclosures of many companies, the study explored International Financial Reporting Standard (IFRS) disclosures and the dynamics of climate change. This disclosure motivates investors by informing them about climate solutions and how the company is building its resilience against climate impacts so that they can make informed investment decisions. The data is collected from JSE-listed manufacturing companies using Refinitiv Eikon, using a historical period from 2005 to 2022. The analysis uses descriptive statistics involving dissimilar econometric techniques such as the panel data dependence technique, pooled multivariate regression, Generalised Method of Moments (GMM), feasible generalised least squares and Pooled Fixed and Random effects. The study found a cross-sectional dependence among the identified dynamics.